KEWIRAUSAHAAN PETANI DAN KINERJA USAHATANI CABE DAN PADI DI KABUPATEN SLEMAN PROPINSI DIY - , DARMADJI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Few studies have been conducted on farmersâ entrepreneurship, especially associated with farm performance that analysis of five indicators at once, productivity, profits, output prices, technical efficiency, and competitive advantage. So far, farm performence more associated with technical aspects of farming. Therefore, the main motivation of this study is to prove whether the farmersâentrepreneurship could be an alternative approaches to increase farm performance. The aim of this research are: (1) to find the effect of internal and external environmental factors, which consists of individual factors, social, economic, physical and institutional environment to the farmersâentrepreneurship, (2) to find the effect of farmersâentrepreneurship on the farm performance, management capacity, technical and biological processes, and (3) to find chili and rice farmersâentrepreneurship . Object of this study is the curly red chilli farmers at the Wukirsari and Argomulyo village, Cangkringan sub-district and rice farmers with SRI farming system at of Madurejo village, Prambanan sub-district, Sleman regency, Yogyakarta Province. This study was cunducted using a multilevel anlysis with Structural Eqution Model (SEM) Based on the analysis can be shown that: 1.Environmental factors that gave influence to the chilli farmersâ entrepreneurship are social and economic environmental, while environmental factors that gave influence to the rice farmers entrepreneurship are economic and physical environment. The social, economic and physical environment gave direct impact toward farmersâ entrepreneurship, and indirect affect to management capacity, technical biological processes, farm performance, and also to each indicator of all three variables. 2. Farmersâ entrepreneurship of chilli and rice farmer gave influence to farming performance, management capacity, and biological and technicals process. Farmersâ entrepreneurship also gave direct influence to farming performance, and indirect influence to farming performance. The indirect influence can throughthe management capacity or biological technics process. Through its indirect influence, the increasing of farming performance in biological technics process gave bigger influence to farming performance, both to chilli and rice farmer. 3.The entrepreneurship of chilli farmer is higher than rice farmerâs. Chilli farmer entrepreneurship can be categorized on high level, while rice farmer entrepreneurship already on high enough category.